2014
DOI: 10.1186/1746-1596-9-117
|View full text |Cite
|
Sign up to set email alerts
|

Significance of 18 F-FDG PET and immunohistochemical GLUT-1 expression for cardiac myxoma

Abstract: Cardiac tumours are relatively rare and are difficult to diagnose merely with imaging techniques. We demonstrated an unusual case of left atrial myxoma, displaying the successful detection by positron emission tomography using 2-deoxy-2-[18 F] fluoro-D-glucose (18 F-FDG PET), correlated closely to more intense and enhanced immunoreactivity with glucose transporter-1 (GLUT-1) in a substantial number of cardiac myxoma cells. Further prospective studies are needed to validate the significance of 18 F-FDG PET find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Histologically, the CM exhibit unique heterogeneous features with myxoma cells scattered in a myxoid stroma. The tumor cells are in single cells, cord-like, pseudo-vascular or vasoformative patterns [42] . The spindle tumor cells without significant atypia surround small blood vessels and scattered lymphoplasmacytic, histiocytic cells, and fibroblastic cells in the myxoma tumor microenvironment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Histologically, the CM exhibit unique heterogeneous features with myxoma cells scattered in a myxoid stroma. The tumor cells are in single cells, cord-like, pseudo-vascular or vasoformative patterns [42] . The spindle tumor cells without significant atypia surround small blood vessels and scattered lymphoplasmacytic, histiocytic cells, and fibroblastic cells in the myxoma tumor microenvironment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On PET-CT imaging, cardiac myxoma can show variable 18 F-FDG uptake. [ 9 13 14 ] Therefore, making a diagnosis just on basis of 18 F-FDG uptake could be fallacious. Contrast-enhanced MRI can be very helpful in such circumstances, as in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET is taken up into cells by GLUTs on the cell membrane like glucose and is phosphorylated by hexokinase; however, FDG-6-phosphate cannot proceed along the glycolytic pathway and is trapped within the tumor cell and then imaged by PET (41). Many experimental and clinical studies have reported that predominant expression of GLUT1 has been demonstrated in several FDG-PET positive malignant tumors, including malignant melanoma (42), lymphoma (43), breast cancer (44), pancreatic cancer (45), and primary non-small cell lung cancers (46), as well as benign tumors, including salivary gland pleomorphic adenomas (47) and cardiac myxoma (48). Dhaval Patel et al reported that GLUT3 overexpression in cortisol-secreting adrenal adenomas likely accounts for increased PET uptake (6).…”
Section: Discussionmentioning
confidence: 99%